2016
DOI: 10.1039/c6ta02825j
|View full text |Cite|
|
Sign up to set email alerts
|

Photochemical reduction of carbon dioxide coupled with water oxidation using various soft-oxometalate (SOM) based catalytic systems

Abstract: We report soft-oxometalate catalytic systems based on various metal oxide catalysts to oxidize H2O and utilize the generated H+s and e−s for reduction of CO2 with a TON of 1366 (effectively 1.4 x 106).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 70 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…We demonstrated earlier that such a micro-bubble formed on a glass substrate drives self assembly of mesoscopic material in an aqueous dispersion due to hydrodynamic (Marangoni) flows caused by the temperature (and the resultant surface tension) gradient across the bubble. 21 At the core of the process is a soft oxometalate (SOM) material [22][23][24][25][26] which absorbs at the laser wavelength of 1064 nm to form a micro-bubble. SOMs self-assembled at the bubble base subsequently undergo a phase transition from the soft to crystalline state 21 as the bubble is translated by the optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated earlier that such a micro-bubble formed on a glass substrate drives self assembly of mesoscopic material in an aqueous dispersion due to hydrodynamic (Marangoni) flows caused by the temperature (and the resultant surface tension) gradient across the bubble. 21 At the core of the process is a soft oxometalate (SOM) material [22][23][24][25][26] which absorbs at the laser wavelength of 1064 nm to form a micro-bubble. SOMs self-assembled at the bubble base subsequently undergo a phase transition from the soft to crystalline state 21 as the bubble is translated by the optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…Following Kozik's work,, we have reported that [CoSiW 11 O 39 ] 6– is an electrocatalyst in dichloromethane for the two electron reduction of carbon dioxide to CO, but also, in the presence of acid, to a very seldom observed four electron reduction product, formaldehyde . Besides being the catalytic species, another role for the POM as an electron/proton relay has also been recently proposed …”
Section: Introductionmentioning
confidence: 83%
“…We have recently shown that soft oxometalates based on several different oxometalates can act as active catalyst for photo chemical oxidation of water without the need of a photosensitizer and a sacrificial electron donor , Further CO 2 can be transformed into other energy dense organic compounds like formic acid and formaldehyde by H 2 O in presence of light using SOMs . In the overall process, the SOM based catalyst oxidizes water to generate oxygen, protons and electrons.…”
Section: Introductionmentioning
confidence: 99%